2019
DOI: 10.3390/met9030284
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Residual Stress on Fatigue Weak Areas and Simulation Analysis on Fatigue Properties Based on Continuous Performance of FSW Joints

Abstract: The fatigue weak area of aluminum alloy for a friction stir-welded joint is investigated based on the hardness profile, the residual stress measurement and the simulation analysis of fatigue property. The maximum residual stresses appeared at the heat-affected zone of the joint in the fatigue damage process, which was consistent with the fracture location of the fatigue specimen. The fatigue joint model of continuous performance is established ignoring the original negative residual stress; considering that it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…These stresses, however, altered during loading cycles and affected fatigue strength noticeably [19]. Sun et al [34] showed that the residual stresses induced by the FSW operation, especially those appeared in the upper surface over cyclic process, impacted fatigue and cracking. The STA heat treatment as a post-processing step on the aluminum welded joint noticeably reduced tensile residual stresses due to the welding process and formed a more uniform microstructure within the HAZ.…”
Section: Fracture Surfaces Of Failed Jointsmentioning
confidence: 99%
“…These stresses, however, altered during loading cycles and affected fatigue strength noticeably [19]. Sun et al [34] showed that the residual stresses induced by the FSW operation, especially those appeared in the upper surface over cyclic process, impacted fatigue and cracking. The STA heat treatment as a post-processing step on the aluminum welded joint noticeably reduced tensile residual stresses due to the welding process and formed a more uniform microstructure within the HAZ.…”
Section: Fracture Surfaces Of Failed Jointsmentioning
confidence: 99%
“…It can significantly impact the fatigue lifetime of a structure. Compressive residual stress increases fatigue lifetime by delaying crack growth, and tensile residual stress reduces fatigue lifetime by expediting crack initiation and propagation [1,2]. To accurately estimate the fatigue lifetime, therefore, the residual stress needs to be evaluated correctly.…”
Section: Introductionmentioning
confidence: 99%